SHM_415393_HST_3D Stone Boat Axe - Qallaki, Ylber; Strandberg, Caroline; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a Middle Neolithic stone boat axe collected from Broby in Skåne, currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=690

Link to Sök I Samlingarna

https://samlingar.shm.se/object/8EA4688A-BF71-461E-97C5-AB31659B993B
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; Archaeology/history; History and archaeology; Dynamic Collections; Swedish Middle Neolithic; Broby; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi